How Do Elementary Teachers Study and Learn from a Multimedia Model of Reading Development? An Exploratory Eye-Tracking Study - Beach, Pamela; Kirby, John; McDonald, Pamela; McConnel, Jen (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
This exploratory study used eye-tracking methodology to examine how elementary teachers study a multimedia model of reading development. Seven experienced teachers and 11 pre-service teachers participated. Visual attention, prior knowledge, and post-task scores were analyzed using quantitative and qualitative methods. Significant differences between the two groups were found with respect to fixations, scan paths, and pre- and post-task scores. Where experienced teachers focus their attention and the paths of their visual behaviour can inform the design of material that supports novice teachers’ understanding of how children learn to read. Keywords: teacher learning, multimedia learning, eye-tracking methodology, reading development, reading instruction